2018
DOI: 10.5267/j.esm.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar alloys (AA6082/AA5083) joining by FSW and parametric optimization using Taguchi, grey relational and weight method

Abstract: This work is focused on the influence of different friction stir welding (FSW) parameters on AA6082 T-6 and AA5083-O alloys welding quality, by using Taguchi, Grey Relational and Weight Method. Four welding parameters were investigated, namely tool rotation speed (TRS), welding speed (WS), tool pin profile (TPP) and shoulder diameter (SD). The optimized setting of these input parameters was investigated so that weld parts quality could be optimized. Analysis of variance (ANOVA) was used to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Dealing with the FSW process, most of the previous research works are focused on linear welding of plates (such as lap, butt and T‐joint welds) for different alloys 3–15 . However, reliable and practical usage of this technique for joining cylinders, pipes and tubes requires a suitable and optimized orbital FSW on cylindrical shells.…”
Section: Introductionmentioning
confidence: 99%
“…Dealing with the FSW process, most of the previous research works are focused on linear welding of plates (such as lap, butt and T‐joint welds) for different alloys 3–15 . However, reliable and practical usage of this technique for joining cylinders, pipes and tubes requires a suitable and optimized orbital FSW on cylindrical shells.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the TRS and WS significantly influenced the responses. Jain et al [13] examined the influence of four FSW important parameters (TRS, WS, TPP, and SD) on different FSW of AA6082 T6 and AA5083-O alloys utilizing the Taguchi's grey relational weight method. They concluded from the results that the optimum UTS was achieved for the TRS of 1200 rpm, WS of 35 mm/min, and SD of 16 mm.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these advantages, FSSW is used to weld lightweight materials, especially aluminum alloys. 58 Two review studies published by Pan 9 and Yang et al. 10 provided comprehensive data on microstructures, mechanical properties, and the fatigue behavior of FSSW in different materials.…”
Section: Introductionmentioning
confidence: 99%